2023
DOI: 10.3390/jcm12175759
|View full text |Cite
|
Sign up to set email alerts
|

The Yin and the Yang of Hemostasis in End-Stage Liver Disease

Fuat H. Saner,
Ecaterina Scarlatescu,
Dieter Clemens Broering
et al.

Abstract: Patients with end-stage liver disease (ESLD) undergoing liver transplantation (LT) are prone to thromboses both while on the waiting list and in the perioperative period. This hypercoagulability is associated with significant endothelial dysfunction (ED) due to nitric oxide dysregulation. ED and increased thrombin generation are the main factors responsible for this hypercoagulability. Sepsis alone can significantly alter a patient’s coagulation profile. In combination with ESLD, however, sepsis or septic shoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 88 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…It has been demonstrated that in the population of hospitalized patients with CLD who have been acutely decompensated, thrombin generation (TG) is significantly increased, which significantly increases the risk of thromboses. This is even more pronounced in patients with ACLF [92]. However, significant fibrinolysis driven by sepsis-related organ failure in patients with ACLF might balance this prothrombotic effect [93].…”
Section: The Dynamics Of Coagulation In Patients With Aclfmentioning
confidence: 99%
“…It has been demonstrated that in the population of hospitalized patients with CLD who have been acutely decompensated, thrombin generation (TG) is significantly increased, which significantly increases the risk of thromboses. This is even more pronounced in patients with ACLF [92]. However, significant fibrinolysis driven by sepsis-related organ failure in patients with ACLF might balance this prothrombotic effect [93].…”
Section: The Dynamics Of Coagulation In Patients With Aclfmentioning
confidence: 99%
“…We congratulate you on a quality review of the article on hemostasis in end-stage liver disease by Saner FH et al [ 1 ]. Early in the article, the authors focus on the fact that many patients with end-stage liver disease have a tendency for thrombosis and hypercoagulability.…”
mentioning
confidence: 99%